2019
DOI: 10.3382/ps/pey324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of experimental Ornithobacterium rhinotracheale infection along with live infectious bronchitis vaccination in broiler chickens

Abstract: Ornithobacterium rhinotracheale (ORT), a bacterium causing respiratory tract infection, has led to a significant problem in the intensive poultry production in Egypt. Polymerase chain reaction-amplified 784bp specific ORT DNA fragments were found in 7 ORT isolates from lungs, air sacs, and tracheas of commercial broilers or layers in Egypt in 2015. The objective of this study was to investigate the role of the live variant IBV 4/91 with ORT infection. A total of 120 14-d-old broiler chickens (Cobb 500) were eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
1
20
0
2
Order By: Relevance
“…Generally, an attenuated vaccine is not recommended due to ORT pathogenicity. In Egypt, Ellakany et al investigated the role of a live variant IVB 4/91 vaccine in ORT infection and revealed that its use can simultaneously increase the pathogenicity of ORT [93]. However, one study evaluated the use of a live, temperature-sensitive mutant vaccine administered by oculonasal instillation in one-day-old turkey.…”
Section: Vaccinationmentioning
confidence: 99%
“…Generally, an attenuated vaccine is not recommended due to ORT pathogenicity. In Egypt, Ellakany et al investigated the role of a live variant IVB 4/91 vaccine in ORT infection and revealed that its use can simultaneously increase the pathogenicity of ORT [93]. However, one study evaluated the use of a live, temperature-sensitive mutant vaccine administered by oculonasal instillation in one-day-old turkey.…”
Section: Vaccinationmentioning
confidence: 99%
“…ORT can cause retarded growth, decreased egg production, and increased mortality and has been associated with avian respiratory disease. Viral infections caused by avian metapneumovirus, infectious bronchitis virus, and Newcastle disease virus and bacterial infections caused by Avibacterium paragallinarum , Bordetella avium , and Escherichia coli can cause severe clinical symptoms when coinfected with ORT ( Ellakany et al., 2019 ). The severity of ORT depends on the strain pathogenicity and other factors such as age, coinfections, and management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Similar microscopic changes were observed in the trachea of 60-day-old quails with ornithobacteriosis, which were characterized by slight degeneration and desquamation of the mucosal epithelium, edema of the lamina propria, edema and congestion, hemorrhages of varying severity and incendiary cell infiltration (Kapakin et al, 2013). Other studies three days after experimental infection of broiler chickens aged 14 days with the causative agent of ornithobacteriosis established: tracheal mucosa with signs of catarrhal tracheitis, goblet cell hyperplasia, lymphocyte infiltration, loss of cilia, hyperplasia of the mucous membrane and glandular epithelium, stagnant phenolmena and infiltration by mononuclear cells (Ellakany et al, 2019). In the spleen, diffuse parenchymal edema and a decrease in the number of lymphocytes in lymphoid follicles were noted.…”
Section: Discussionmentioning
confidence: 94%
“…Bacteriological studies are essential for the diagnosis, since microscopic changes in a number of diseases can be similar. In particular, studies by Hany Ellakany and Hatem Hamid have established that similar microscopic changes occur for mycoplasmosis and ornithobacteriosis, and the causative agents of these disea-ses can develop together, mutually reinforcing the pathogenic effect (Ellakany et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation